2022
DOI: 10.1021/acs.jpcc.2c03310
|View full text |Cite
|
Sign up to set email alerts
|

Influence of CO2 on Nanoconfined Water in a Clay Mineral

Abstract: Developing new technologies for carbon sequestration and long-term carbon storage is important. Clay minerals are interesting in this context as they are low-cost, naturally abundant, can adsorb considerable amounts of CO 2 , and are present in storage sites for anthropogenic carbon. Here, to better understand the intercalation mechanisms of CO 2 in dehydrated and hydrated synthetic Na-fluorohectorite clay, we have combined powder X-ray diffraction, inelastic and quasi-elastic neutron scattering, and density f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 67 publications
0
19
0
Order By: Relevance
“…Li-Hec shows a much more sluggish dehydration behavior compared to Na-Hec. For Na-Hec, only a very limited residual water population has been observed by INS (inelastic neutron spectroscopy) to be left in the sample after dehydration to 145 °C . Recent experiments on a Li-Hec from Corning found that dried Li-Hec contains tightly bound water molecules that have a significantly higher adsorption energy, 225 kJ/mol compared to 31 kJ/mol for the more loosely bound water population in the sample.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Li-Hec shows a much more sluggish dehydration behavior compared to Na-Hec. For Na-Hec, only a very limited residual water population has been observed by INS (inelastic neutron spectroscopy) to be left in the sample after dehydration to 145 °C . Recent experiments on a Li-Hec from Corning found that dried Li-Hec contains tightly bound water molecules that have a significantly higher adsorption energy, 225 kJ/mol compared to 31 kJ/mol for the more loosely bound water population in the sample.…”
Section: Resultsmentioning
confidence: 99%
“…Na-Hec ( Figure 1 c), which is observed to have a basal spacing of 9.6 Å, in line with previous observations of dehydrated Na-Hec, 17 does not swell in response to CO 2 , and there are no changes in the peak observed after CO 2 exposure, again confirming our previous reports. 30 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The interaction of water with clay mineral surfaces has been subject to intense study for decades, but has received heightened interest in the past 20 years. Much of the recent interest stems from an incomplete understanding of the complementary, but often competing, roles played by hydrating counter ions and the clay mineral interlayer surface itself, various pore sizes present within clay gels, and how each of these influence reactivity in various contexts, e.g., as catalysts, adsorbents, or carriers . Indeed, water interaction with minerals in general is perhaps a defining feature of the evolution of Earth , and has proven to be an important aspect of current interplanetary exploration and study. Samples returned to Earth from the Ryugu asteroid by the Hayabusa spacecraft, for example, have already been analyzed finding CO 2 -bearing water inclusions to be present within a pyrrhotite crystal …”
Section: Introductionmentioning
confidence: 99%